Sosialisasi Penggunaan Kantong Belanja Ramah Lingkungan sebagai Upaya Pengurangan Sampah Plastik bagi Pelaku UMKM - Komang Widhya Sedana Putra P; Martina Angelica Oktaviani Damai; Kadek Wulandari Laksmi P; IGN Oka Ariwangsa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The negative impact of single-use plastic bags is alarming, especially concerning Micro, Small, and Medium Enterprises (MSMEs). Bags that are made from plastic waste are non-biodegradable and harmful to the environment as well as to ecosystems. Hence, it is critical to educate MSME business owners on the need to replace plastic with eco-friendly shopping bags. Objective: The goal of this program is to teach MSME entrepreneurs the negative impacts of plastic waste and provide them with the option of more sustainable reusable bags. Method: The program was implemented using a door-to-door method of socialization targeting MSME business owners in Desa Padangsambian Klod. It consisted of direct contact with business owners to inform them about the environmental impacts of waste created from single use plastics and the advantages of using reusable shopping bags. Eco-friendly shopping bags were distributed along with brochures to encourage the rest of the community to adopt them in their businesses. Result: This initiative helped MSME entrepreneurs understand the issues surrounding plastic waste as well as their eco-friendly alternatives. The participants expressed interest and willingness to incorporate these reusable bags into their everyday business activities. Conclusion: The outcome of this case indicates that the door-to-door method can be used to increase awareness of MSME entrepreneurs on the need to reduce plastic waste. With adequate follow up steps this program can act as a starting point in nurturing a business culture that is environmentally proactive.